Milk and wheat proteins as emulsifiers on chicken hotdog - Santiago, Richelda Amante
Chicken hotdogs were developed from chicken breast meat, chicken thigh meat and pork meat. The variable in this study was the kind of protein emulsifier added and its subsequent effect on product quality characteristics. Results of the objective and subjective tests showed that the best product was that where wheat protein--a vegetable protein--was used. The finished product showed a moderately tender to very tender texture, slight to moderate juiciness, moderately smooth mouthfeel and with an ideal or true chicken flavor. The rating for over-all acceptability was "like moderately" to "like very much". Moisture content was at 52.06% and water-holding capacity was 44.8%. Emulsion was stable even after two and a half months of frozen storage, and microbial count was very low with respect to acceptable levels.